Strategic Construction of Brand Image by the Faculty of Science and Technology at Universitas Islam Negeri Sumatera Utara in Strengthening Public Trust - Nurhanifah Nurhanifah; Mirna Annifah Hasibuan; M. Agung Rahmadi (Lembaga Pengembangan Kinerja Dosen, 2026)
The construction of brand image has become a strategic imperative for Islamic higher education institutions in the era of global competition. Prior research has examined the impact of educational institutional branding on academic performance (Karsono et al., 2021). However, a gap remains regarding the explicit integration of Islamic values into science and technology branding. This study aims to explore the brand image strategies of the Faculty of Science and Technology at UIN North Sumatra in building public trust. This research employs a qualitative descriptive approach with purposive sampling, involving five key informants: the Dean of FST, the Vice Dean III, the Head of Administrative Affairs, and two students. Data were collected through in-depth interviews, participatory observation, and documentation. The research findings identify four strategic pillars: (1) leadership-student synergy in digital dissemination representing the concept of syura; (2) integration of the wahdatul ulum paradigm and rahmatan lil alamin principle in inclusive service delivery; (3) optimization of the official website as an instrument of transparency; (4) consistency in multi-stakeholder communication. Thus, it can be understood that a branding model harmonizing academic excellence with Islamic values in the science-technology context serves as a competitive differentiator, enriching the strategic branding literature of Islamic higher education and demonstrating that authentic integration of religious values strengthens institutional positioning at national and global levels.